Review: Senyawa Bahan Alam Terestrial dengan Aktivitas Antimalaria - Jefry Presson (Saintek Lahan Kering, 2018)
Malaria is still a major public health problem that urgently needs some new treatments due to the development of resistance by the most dangerous parasitic species, Plasmodium falciparum. The parasite responsible to malaria which claimed as the most lethal disease are endless handled due to increasing prevalence. Based on World Malarial Report in 2015 by WHO, about 214 million cases of malaria and 438,000 death occurred among them. Moreover, discontinue of artemisinin because of its resistance in Southeast Asia indicate that the discovery of new antimalarial drug is highly important. This review present recent research and development progress in antimalarial drug discovery from natural sources especially on terrestrial.